2022
DOI: 10.1002/cey2.210
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐doped Ag/Ni2(CO3)(OH)2 hierarchical microtubes for highly efficient water oxidation

Abstract: Doping of foreign atoms and construction of unique structures are considered as effective approaches to design high-activity and strongdurability electrocatalysts. Herein, we report Fe-doped nickel hydroxide carbonate hierarchical microtubes with Ag nanoparticles (denoted Ag/ NiFeHC HMTs) through hydrolysis precipitation process. Experimental tests and density functional theory calculations reveal that Fe doping can tune the electron configuration to enhance the conductivity, markedly improve the electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…3,4 In particular, NiFe-LDH is deemed as a promising non-noble metal OER electrocatalyst due to its special layered structure and adjustable components. 5,6 At present, the modified methods for NiFe-LDH mainly concentrate on electronic regulation and exposure of active sites. 7−9 However, these strategies overlook the fact that NiFe-LDH is a typical antiferromagnetic (AFM) material with highly tunable electron orbitals, thereby providing a structural basis for tuning spin states of the catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In particular, NiFe-LDH is deemed as a promising non-noble metal OER electrocatalyst due to its special layered structure and adjustable components. 5,6 At present, the modified methods for NiFe-LDH mainly concentrate on electronic regulation and exposure of active sites. 7−9 However, these strategies overlook the fact that NiFe-LDH is a typical antiferromagnetic (AFM) material with highly tunable electron orbitals, thereby providing a structural basis for tuning spin states of the catalyst.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, the anodic OER involves a complex four-electron transfer process and the conversion of diamagnetic molecules (H 2 O, OH – ) into paramagnetic molecules (O 2 ), resulting in sluggish reaction kinetics and high overpotential . Therefore, researchers have developed numerous low-cost and efficient transition metal-based electrocatalysts to enhance the OER catalytic activity. , In particular, NiFe-LDH is deemed as a promising non-noble metal OER electrocatalyst due to its special layered structure and adjustable components. , At present, the modified methods for NiFe-LDH mainly concentrate on electronic regulation and exposure of active sites. However, these strategies overlook the fact that NiFe-LDH is a typical antiferromagnetic (AFM) material with highly tunable electron orbitals, thereby providing a structural basis for tuning spin states of the catalyst . Therefore, it is necessary to design a strategy to regulate the electron spin states of NiFe-LDH.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, due to the poor electronic conductivity and limited active sites of NiO, it usually leads to high overvoltage and poor cycle performance of Li–O 2 batteries . A few recent studies have shown that heteroatom doping can tune the surface electronic structure in order to improve electronic conductivity and build interface defects to expose more active sites, which are beneficial for enhancing catalytic activity. , Noble metal catalysts (such as Pt, Au, Ag, etc.) have a large number of unfilled d-electron orbitals and surface properties, which show higher catalytic activity and selectivity than traditional catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The peak of Fe 2p 1/2 was resolved into three peaks (Fig. S4b, ESI †), corresponding to the Fe 2+ , Fe 3+ and satellite peak, 20 respectively. Examining the Ni 2p spectra (Fig.…”
mentioning
confidence: 99%